PENGEMBANGAN MEDIA BUSY BOOK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AWAL SISWA DI SEKOLAH DASAR - Dewi Sartika; Abdul Hakim; Farida Febriati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Selecting appropriate learning media to support the learning process remains a common challenge for teachers. This study aimed to analyze the need for busy book media, design and validate the product, assess its practicality, and evaluate its effectiveness in improving elementary school students’ early reading skills. A mixed-methods approach was employed using the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through questionnaires administered to an Indonesian language teacher and 21 randomly selected students. The findings indicated that the busy book media was highly needed and achieved very high validity scores from media experts (92.6%) and content experts (83.3%). The practicality level was categorized as very practical, ranging from 92% to 94%. Posttest results showed a significant improvement compared to pretest scores, indicating high effectiveness. Therefore, the busy book media is feasible and effective as an alternative medium for early reading instruction. This study implies that busy books support student-centered learning by encouraging active student engagement.